IUTAM: A Short History - Dr. Stephen Juhasz (Springer Nature, 2016)
This volume presents the historical development of IUTAM, which began in Innsbruck in 1922 where the first IUTAM conference took place. These conferences have been held every four years with great success: the next will take place in Grenoble in 1988. This volume is dedicated to Professor Theodore von Karman (1881-1963), who has contributed greatly to the foundation of IUTAM.